LATITUDINAL STRUCTURE OF TRENDS AND EFFECT OF SOLAR ACTIVITY IN STRATOSPHERIC NO2 - Gruzdev A.N. (My University, 2007)
The estimates of linear trends in the total content (TC) of NO2 as functions of latitude are first presented in this paper. The estimates of trends for several sites of NO2 observations were obtained earlier. Positive NO2 trends content (per decade) were reported from the following stations: approximately 5% at Station Lauder, New Zealand; approximately 6% at Station Jungfraujoch, Switzerland; and within 5–7% at Station Issyk-Kul, Kyrgyzstan. These trends are based on the data of observations during 17–21 yr. For a shorter period of measurements (13 yr) at Zvenigorod Scientific Station of the Institute of Atmospheric Physics, Russian Academy of Sciences, large (by module) values of the negative trend in TC of NO2 (–12% per decade) were obtained.